Ceftolozane/Tazobactam for Treating Children With Exacerbations of Cystic Fibrosis Due to Pseudomonas aeruginosa: A Review of Available Data - Silvia Garazzino; Elena Altieri; Erika Silvestro; Giulia Pruccoli; Carlo Scolfaro; Elisabetta Bignamini (Frontiers Media S.A., 2020)
Ceftolozane-tazobactam is a novel fifth-generation cephalosporin/β-lactamase inhibitor combination recently approved for treatment of both complicated intra-abdominal and urinary tract infections in adults. Considering its potent bactericidal activity against Pseudomonas aeruginosa, it might represent an important option also for treating children with exacerbations of cystic fibrosis due to Pseudomonas aeruginosa when other alternative treatments have been exhausted. We hereby review available data on the use of ceftolozane-tazobactam in children, focusing on cystic fibrosis.